Modula????o de fatores anti-inflamat??rios em modelo de les??o traum??tica em tend??o de Aquiles de rato - Casalechi, Heliodora Le??o (2015)
Tendinitis is a common disorder of the musculoskeletal system with multiple pathological manifestations. Although most tendons have the ability to spontaneously repair after injury, scar tissue is formed that can prevent the tendon to perform normal functions. Studies have been conducted using phototherapy in different health areas, using low-intensity lasers and LEDs. However, there are few studies with LEDs therapy. The aim of this study was to investigate the effect of phototherapy with Laser (830nm) and LED (945nm) in the repair process of the calcaneus tendonitis in rats. The inflammation was induced by controlled contusion in the medial region of the Achilles tendon of the animals. Was used 112 young male Wistar rats (240 ?? 20g), divided into 14 groups with two different experimental periods. Groups CONT (control group), TEND (tendinitis group) during periods 7 and 14 days, LEDT (LED therapy, from th to 7th day and from 1th to 14th day), and LEDT delay (LED therapy from 7th to 14th day). The therapy was initiated 12h after the tendinitis induction, with a 48h interval between irradiations (dose 6J/point). The control animals received simulation of treatment; the same experimental design was used for Laser treatment. All groups were euthanized on the 7th or 14th day after the induction. The tendons were dissected, extracted, and sent for analysis. Were performed biomechanical and histological analysis to evaluate neutrophils and collagen, were also quantitated the inflammatory mediators by real-time polymerase chain reaction (RT-PCR) and the IL-6 and TNF- ?? levels by ELISA. The results showed that treatments with low-intensity lasers in the parameters used and the times studied reduces migration of inflammatory cells and improves the quality of repair, but the LED even decreasing the inflammation was not effective of biomechanical properties of tendon tissue.